Point-prevalence survey of antibiotic use at three public referral hospitals in Kenya. - Sylvia Omulo; Margaret Oluka; Loice Achieng; Eric Osoro; Rosaline Kinuthia; Anastasia Guantai; Sylvia Adisa Opanga; Marion Ongayo; Linus Ndegwa; Jennifer R Verani; Eveline Wesangula; Jarred Nyakiba; et al. (PLoS ONE)
Antimicrobial stewardship encourages appropriate antibiotic use, the specific activities of which will vary by institutional context. We investigated regional variation in antibiotic use by surveying three regional public hospitals in Kenya. Hospital-level data for antimicrobial stewardship activities, infection prevention and control, and laboratory diagnostic capacities were collected from hospital administrators, heads of infection prevention and control units, and laboratory directors, respectively. Patient-level antibiotic use data were abstracted from medical records using a modified World Health Organization point-prevalence survey form. Altogether, 1,071 consenting patients were surveyed at Kenyatta National Hospital (KNH, n = 579), Coast Provincial General Hospital (CPGH, n = 229) and Moi Teaching and Referral Hospital (MTRH, n = 263). The majority (67%, 722/1071) were ≥18 years and 53% (563/1071) were female. Forty-six percent (46%, 489/1071) were receiving at least one antibiotic. Antibiotic use was higher among children <5 years (70%, 150/224) than among other age groups (40%, 339/847; P < 0.001). Critical care (82%, 14/17 patients) and pediatric wards (59%, 155/265) had the highest proportion of antibiotic users. Amoxicillin/clavulanate was the most frequently used antibiotic at KNH (17%, 64/383 antibiotic doses), and ceftriaxone was most used at CPGH (29%, 55/189) and MTRH (31%, 57/184). Forty-three percent (326/756) of all antibiotic prescriptions had at least one missed dose recorded. Forty-six percent (204/489) of patients on antibiotics had a specific infectious disease diagnosis, of which 18% (37/204) had soft-tissue infections, 17% (35/204) had clinical sepsis, 15% (31/204) had pneumonia, 13% (27/204) had central nervous system infections and 10% (20/204) had obstetric or gynecological infections. Of these, 27% (56/204) had bacterial culture tests ordered, with culture results available for 68% (38/56) of tests. Missed antibiotic doses, low use of specimen cultures to guide therapy, high rates of antibiotic use, particularly in the pediatric and surgical population, and preference for broad-spectrum antibiotics suggest antibiotic use in these tertiary care hospitals is not optimal. Antimicrobial stewardship programs, policies, and guidelines should be tailored to address these areas.